QUANTITATIVE EVALUATION OF IMMUNOCYTES AND INTERLEUKIN-17 LEVELS IN SALIVA FROM SMOKERS AT THE EARLY STAGES OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - E. I. Altynbaeva (SPb RAACI, 2014)
The study was focused on identification of disorders in immune homeostasis in the mucosalivary area, using cytofluorometric analysis of immune cell populations and quantitative enzyme immunoassay for interleukin-17 in saliva of radiochemical facility workers with a history of smoking, being at initial stages of chronic obstructive pulmonary diseases (COPD) without exacerbations. We have observed a cohort of COPD patients (144 workers), as well as a group of 264 smoking individuals without any signs of COPD. The study and control groups have been matched by age, gender, working conditions, smoking index and clinical history. During the last ten years, the persons under study were subject to a regular follow-up. The current study included twenty-three patients from the main group and ten individuals from the group of comparison. Analysis of immunocytes in saliva was peformed by means of flow cytometry. The patients for laboratory studies were selected in a random manner. Total amounts of leukocytes was measured in saliva, providing a mean value of 2.4106/ml, followed by filtration of saliva through porous filters (Becton Dickinson). Cytofluorimetric analysis was performed be means of BD FACSCanto II machine, using a kit of appropriate monoclonal antibodies, thus allowing of a four-colour fluorescence analysis. The salivary immune cell subpopulations were scored with viable cells, positive for CD4+. A significant increase in amounts of CD+CD8- (25.85% versus 1.4% in the control group, p = 0.049) and in CD+CD+ (3.3% versus 0.6%, p = 0.049) was noted in COPD patients, hence presuming an increase in total amounts of T-lymphocytes and T-helpers, without any enhancement of cytotoxic cell populations in the mucosalivary region, being permanently exposed to tobacco smoke in the smokers with COPD. The obtained findings let us to assume an involvement of CD+CD+ lymphocytes in pathogenesis of inflammatory alterations at COPD. An increased level of IL-17 was revealed in COPD patients group, versus those smokers, who had no clinical signs of COPD, thus suggesting activation of secretory functions in a subpopulation of CD+CD+ lymphocytes (i.e., Th17).